Menelusuri Sejarah Penerapan Gugatan Citizen lawsuit Dalam Perspektif Hukum Acara Perdata di Indonesia Negara Mayoritas Islam - Carwan, Carwan; Lestari, Sari Indah; Santoso, Tyas Sri Eka Santoso; Satory, Agus Satory (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
At the stage of filing a case, the term used is a legal action or lawsuit. A citizen lawsuit is a lawsuit filed on behalf of the public interest against the State authorities. The history of filing a citizen lawsuit originated in cases related to the environment, but over time, citizen lawsuits have been filed in various fields where the State is perceived to have been negligent and violated the rights of citizens. Therefore, it is important to understand the basis for applying the procedure using a citizen lawsuit in civil procedural law in Indonesia. This study aims to explore how a citizen lawsuit can be applied in civil procedural law in Indonesia, viewed from a historical and positive law perspective. This research uses a normative juridical research approach. Citizen lawsuits in Indonesia emerged through the adoption of legal mechanisms from other countries, driven by the activities of Non-Governmental Organizations (NGOs) and Legal Aid Organizations (LBH). The first use of a citizen lawsuit in Indonesia can be seen in Decision 480/PDT/2005/PT.DKI concerning the State's neglect of deported migrant workers in Nunukan by the Malaysian government. Thus, to date, citizen lawsuit cases have been followed by other civil court judges in similar cases, making citizen lawsuits a precedent followed by judges in similar cases